"The teacher explains, I disconnect." Analysis of a methodological change in Compulsory Secondary Education. - Formento Torres, Ana Cristina (2024)
This study arises from the need to address the question that arises when teachers are confronted with the reality of a classroom full of adolescents, sometimes uninterested and quite accustomed to taking on a passive role in their learning: what about the teacher's explanation? To address this, a qualitative research with a multivalent design was conducted with two experimental groups of 14- and 15-year-old adolescents. Cooperative methodology was implemented in the subject of Spanish Language and Literature, with the evaluation tools for the process being the classroom diaries of the student groups, the teacher's diary, and a student focus group. The data were collected during the 2021-2022 academic year at a school in Zaragoza, Spain. The study examines how students organize and manage their cooperative learning, the difficulties they encounter in this process, and the results obtained from an academic, social, and personal perspective. The research findings indicate that effective teamwork and communication are essential elements in the organization, while the difficulties faced are related to assistance, teamwork, and task complexity. The final outcome reveals increased autonomy and activation of learning in the students.